2004
DOI: 10.1115/1.2162183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Turbine Tip Leakage Flow for Flat Tip and Squealer Tip Geometries at High-Speed Conditions

Abstract: The tip leakage flow characteristics for flat and squealer turbine tip geometries are studied in the von Karman Institute Isentropic Light Piston Compression Tube facility, CT-2, at different Reynolds and Mach number conditions for a fixed value of the tip gap in a nonrotating, linear cascade arrangement. To the best knowledge of the authors, these are among the very few high-speed tip flow data for the flat tip and squealer tip geometries. Oil flow visualizations and static pressure measurements on the blade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(42 citation statements)
references
References 16 publications
0
41
0
1
Order By: Relevance
“…Both the cavity tip and the suction-side squealer tip performed better than the flat tip. Cavity tips were also found to produce lower loss than the flat tip in a number of other studies: e.g., Key and Arts [3] and Zhou and Hodson [4]. In terms of mechanical design, the centrifugal loading of a blade with a cavity tip is lower than that of a flat tip, so cavity tips are also preferred from this point of view.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Both the cavity tip and the suction-side squealer tip performed better than the flat tip. Cavity tips were also found to produce lower loss than the flat tip in a number of other studies: e.g., Key and Arts [3] and Zhou and Hodson [4]. In terms of mechanical design, the centrifugal loading of a blade with a cavity tip is lower than that of a flat tip, so cavity tips are also preferred from this point of view.…”
mentioning
confidence: 83%
“…So less of the chord is choked over the cavity tip than over the flat tip. Key and Arts [24] studied the tip-leakage flow characteristics of a flat tip and a cavity tip in a high-speed linear cascade. The cavity tip reduced the leakage flow more effectively than the flat tip.…”
mentioning
confidence: 99%
“…Cavity tips were found to produce lower loss than the flat tip in a number of other studies, e.g. Key and Arts [4] and Zhou and Hodson [5]. In terms of mechanical design, the centrifugal loading of a blade with a cavity tip is lower than that of a flat tip, so cavity tips are also preferred from this point of view.…”
Section: Introductionmentioning
confidence: 95%
“…In a rotating turbine facility, Camci et al (2005) showed that suction-side partial squealers are aerodynamically superior to pressure-side partial ones and channel arrangements. Key and Arts (2006) found at high speed conditions that the cavity squealer tip provides a significant decrease in velocity through the tip gap for h/s = 1.34%. Lee and Chae (2008) studied the effect of cavity squealer rim height (h st ) on the aerodynamic losses in a turbine cascade for h/s = 1.36%.…”
Section: Introductionmentioning
confidence: 91%